Hexaaquamanganese(II) dipicrate dihydrate - Liu, Changying (International Union of Crystallography, 2008)
In the title compound, [Mn(H(2)O)(6)](C(6)H(2)N(3)O(7))(2)·2H(2)O, the manganese cation, on an inversion centre, is coordinated by six water molecules, but the picrate anion has no coordinative interaction with the manganese cation. The anions in the stack are linked via short intermolecular O⋯C (3.013 and 2.973 Å) and C⋯C (3.089 and 3.065 Å) contacts and hydrogen bonds.